Injectable freeze‐dried chitosan‐platelet‐rich‐plasma implants improve marrow‐stimulated cartilage repair in a chronic‐defect rabbit model. (8th March 2019) - Dwivedi, Garima; Chevrier, Anik; Hoemann, Caroline D.; Buschmann, Michael D.
Abstract: Bone‐marrow stimulation (BMS) improves knee‐joint function but elicits incomplete repair. Liquid chitosan (CS)–glycerol phosphate/blood clots have been shown to improve BMS‐based cartilage repair. Platelet‐rich‐plasma (PRP)—a rich source of growth factors and cytokines—improves recruitment and chondrogenic potential of subchondral mesenchymal stem cells. We hypothesised that repair response in a rabbit chronic‐defect model will improve when freeze‐dried CS/PRP is used to augment BMS. Bilateral trochlear defects created in New Zealand white rabbits were allowed to progress to a chronic stage over 4 weeks. Chronic defects were debrided and treated by BMS in second surgery, then augmented with PRP (BMS + PRP) or freeze‐dried CS/PRP implants (BMS + CS/PRP). The quality of 8‐week repair tissue was assessed by macroscopic, histological, and micro computed tomography (Micro‐CT) analysis. ICRS macroscopic scores indicated fibrocartilaginous or fibrous repair in control defects that were improved in the BMS + CS/PRP group. An overall improvement in repair in BMS + CS/PRP group was further confirmed by higher O'Driscoll scores, %Saf‐O and %Coll‐II values. Micro‐CT analysis of subchondral bone indicated ongoing remodelling with repair still underway. Quality and quantity of cartilage repair was improved when freeze‐dried CS/PRP implants were used to augment BMS in a chronic defect model.